Exploring the Challenges and Opportunities of Digital Art in Contemporary Exhibitions on Social Media Platforms: Insights from Practitioners - Taj, InamUllah; Ali, Syed Atef Amjad; Ameen, Maliha (Pakistan Journal of Humanities and Social Sciences, 2024)
This research investigates the multifaceted landscape of electronic art exhibitions on social media platforms in Pakistan, focusing on technological challenges, social media utilization, and global accessibility concerns. Drawing on the Media Aesthetic Theory, Stuart Hall’s Encoding/Decoding model, and Actor-Network this study aims to uncover the challenges and opportunities facing digital art in contemporary social media contexts. Using a semi-structured interview approach, adopted by Pitts (2020) fifteen emerging visual artists were interviewed. The interviews focused on understanding the artists’ perspectives on digital exhibitions, exploring technological innovations, artistic anatomy, and ethical considerations. The findings highlight a synthesis of technological innovations and the complexities of this digital terrain within an inclusive and ethically responsible art ecosystem. Prospects, accounting of respondents' perspectives, include enhanced content moderation, curatorial flexibility, and global reach. Challenges encompass algorithmic bias, lack of training, and financial constraints while ethical quandaries representing respondents' insights pertain to cultural sensitivity, environmental responsibility, and equitable collaboration. The study underlines the complexities of the digital landscape, advocating for an integrative and ethically responsible art ecosystem. Addressing these complexities, digital art practitioners stress the importance of transparency, community engagement, and promotion of innovation in the Pakistani art scene. These insights stress the multifaceted landscape of digital art and social media, with careful maneuvering of ethical and impactful artistic expressions.